Problematika vankomycín rezistentných enterokokov - podstata rezistencie a riziko prenosu zo zvierat na cloveka - Hermanovská, Lýdia; Bardoň, Jan; Čermák, Pavel (Klinicka mikrobiologie a infekcni lekarstvi, 2016)
Enterococci are part of the normal intestinal flora of humans and animals. Under certain circumstances, they are capable of extraintestinal conversion to opportunistic pathogens. They cause endogenous as well as exogenous community and nosocomial infections. The gastrointestinal tract of mammals provides them with favorable conditions for acquisition and spread of resistance genes, for example to vancomycin (van), from other symbiotic bacteria. Thus, vancomycin-resistant enterococci (VRE) become potential reservoirs and vectors of the van genes. Their occurrence in the population of the Czech Republic was first reported by Kolář et al. in 1997. Some variants of the vanA gene cluster carried on Tn1546 which encode resistance to vancomycin are identical in humans and in animals. It means that animals, especially cattle, poultry and pigs, could be an important reservoir of VRE for humans. Kolář and Bardoň detected VRE in animals in the Czech Republic for the first time in 2000. In Europe, the glycopeptide antibiotic avoparcin, used as a growth stimulator, is responsible for selection of VRE strains in animals. Strains of Enterococcus faecium from animals may offer genes of antimicrobial resistance to other enterococci or they can be directly dangerous to human. This is demonstrated by finding isolates of E. faecalis from human patients and from pigs having very similar profiles of resistance and virulence genes. The goal of the paper was to point out the similarity between isolates of human and animal strains of enterococci resistant to vancomycin, and the possibility of their bilateral transfer between humans and animals.
Keywords: skot; Disease Reservoirs; Swine; Česká republika; Animals; Cattle; lidé; enterokoky rezistentní vůči vankomycinu; zdroje nemoci; prasata; riziko; Humans; Vancomycin-Resistant Enterococci; zvířata; Risk; Czech Republic